Design of a Synthetic Zinc Oxide Catalyst over Nano-Alumina for Sulfur Removal by Air in a Batch Reactor - Amer T. Nawaf; Aysar Talib Jarullah; Layth T. Abdulateef (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2019)
Owing to the environmental regulations with respect to sulfur content and continuing challenges of finding a suitable catalyst of such impurity, a driving force for the development of more efficient technologies a deep research on new oxidative catalysts is considered an important issue in fuel quality improvement. Thus, the present study shows a novel percent of nano-catalyst with 18% zinc oxide (ZnO) of active component over nano-alumina that has not been reported in the public domain for sulfur removal from kerosene fuel by air (oxidative desulfurization (ODS) method). Where, such percent of the active component on the nano-alumina helps to add one or two atoms of oxygen to sulfur content in the kerosene. The nano-catalyst (ZnO/nano-alumina-particles composite) is prepared by precipitation of zinc oxide and loaded over nano-alumina in one-step. The activity of the prepared catalyst was tested utilizing ODS process of kerosene fuel by air in a batch reactor. A set of experiments were conducted with a wide range of operating conditions, where the reaction temperature was ranged from 150 to 190ºC, the reaction time from 30 to 50 min and the catalyst weight from 0.4 to 1 g. The experimental results showed that the chemical nature of zinc oxides showed higher conversion (70.52%) at reaction temperature of 190 ºC, reaction time of 50 min, and 1 g catalyst weight used in the batch reactor. A kinetic model related to the sulfur removal from kerosene via ODS process in the batch reactor was also investigated in this study for the purpose of estimating the best kinetic parameters of the relevant reactions. The results showed that the prepared catalyst (ZnO over nano-alumina) can be applied confidently to reactor design, operation and control in addition to improve the fuel quality. Following the kinetic model of ODS process, a very well agreement between the experimental and predicted results is obtained. Copyright © 2019 BCREC Group. All rights reserved